An approach to fever in the returning traveller - Garth K. Brink; John Frean; Albie de Frey (South African Family Practice)
The traveller who presents with fever on return requires a comprehensive assessment. This paper outlines the salient features in assessing these patients. A detailed history, examination and knowledge of diseases prevalent in the areas that were visited is essential if one is to arrive at a diagnosis and institute appropriate treatment or referral. Malaria remains the first differential diagnosis in travellers returning from an endemic area irrespective of precautions taken. The most common illnesses that result in a fever in travellers are presented and a resource list is provided.